“Trabalhar com a morte é não parar de pensar nela”: estudo antropológico sobre as práticas dos profissionais de saúde do hospital Napoleão Laureano com os pacientes com câncer em cuidados paliativos - Silva, Weverson Bezerra (2021)
This work aims to understand the experiences and practices of health professionals who work in the palliative care patients ward at Hospital Napoleão Laureano (HNL), a reference in the treatment of people with cancer in the State of Paraíba. It is a qualitative research, based on participant observation from the perspective of “hospital ethnography”. In view of this, the work provides a description of the field and discusses how health professionals elaborate the meaning of the death of patients who are / are considered “out of therapeutic possibility” (FPT) and how they understand the work of care together to them. The experiences and practices of health professionals lead to thinking about technical aspects as well as highlighting intersubjective dimensions in the meeting of professionals with patients, with their families and in the dialogue with personal experiences of life and death. The consulted literature situates the practices analyzed in the context of the various social movements that have emerged around the world in favor of improving the dying and autonomy of the dying space “a good death”. The demands created by these movements contemplated the individual and his social right to the process of dying, pointing to changes in the process of contemporary death aimed at people under palliative care.